A EDUCAÇÃO MATEMÁTICA COMO CAMPO CIENTÍFICO EM MATO GROSSO DO SUL (1990-2020) - KAMILA DA FONSECA VEIGA CAVALHEIRO LEITE (2025)
The present thesis aimed to provide an overview of the scientific field of Mathematics Education in Mato Grosso do Sul (MS), Brazil, based on the analysis of its symbolic production in academic stricto sensu graduate programs during the period from 1990 to 2020. The focus of the analysis was on theses and dissertations defended in graduate programs in the areas of Teaching, Psychology, and Education, which addressed Mathematics Education as a central theme. The theoretical framework adopted is grounded in Pierre Bourdieu’s studies on the scientific field, exploring concepts such as Symbolic Production, Habitus, Agents, Institutions, and Scientific Capital. The research sought to answer the question: “What singularities of the scientific field of Mathematics Education in MS can be investigated by taking symbolic productions as the axis of analysis?” To this end, the transformations in the scientific field of Mathematics Education in MS over the period were examined, considering aspects such as the number of defended theses and dissertations, research grants and scholarships awarded, emerging thematic trends, and interactions among agents as an expression of the scientific habitus. The results point to a significant expansion of the investigated field, driven primarily by the establishment of the Graduate Program in Mathematics Education at the Federal University of Mato Grosso do Sul (PPGEDUMAT/UFMS), the first stricto sensu graduate program in Mathematics Education in the region. The relationships among agents and the thematic trends mobilized in the productions indicate a research community with heterogeneous characteristics and, at the same time, integrated, demonstrating the dynamism and collaboration among different agents and educational institutions in the process of consolidating the scientific field of Mathematics Education in the state. During the investigated period, the construction of scientific collaboration networks was observed, primarily involving the Federal University of Mato Grosso do Sul (UFMS) and the Catholic University Dom Bosco (UCDB). The singularities of the analyzed field are marked by the academic trajectories of prominent agents in the field’s hierarchy, whose doctoral training took place in France. The subsequent work of these researchers as advisors and mentors of new generations of researchers proved to be an important element in the constitution and characterization of the field of Mathematics Education in Mato Grosso do Sul. These findings corroborate the identification of changes in the perspectives on researcher training in Mathematics Education in the region over the investigated period. Finally, the direct linkage between SBEM-MS and PPGEDUMAT/UFMS, both in their creation and in the activities developed over time, stands out as one of the singular characteristics of this field.